If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(1 + -3y) + -2(10 + -1y) = 10y (1 * 5 + -3y * 5) + -2(10 + -1y) = 10y (5 + -15y) + -2(10 + -1y) = 10y 5 + -15y + (10 * -2 + -1y * -2) = 10y 5 + -15y + (-20 + 2y) = 10y Reorder the terms: 5 + -20 + -15y + 2y = 10y Combine like terms: 5 + -20 = -15 -15 + -15y + 2y = 10y Combine like terms: -15y + 2y = -13y -15 + -13y = 10y Solving -15 + -13y = 10y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-10y' to each side of the equation. -15 + -13y + -10y = 10y + -10y Combine like terms: -13y + -10y = -23y -15 + -23y = 10y + -10y Combine like terms: 10y + -10y = 0 -15 + -23y = 0 Add '15' to each side of the equation. -15 + 15 + -23y = 0 + 15 Combine like terms: -15 + 15 = 0 0 + -23y = 0 + 15 -23y = 0 + 15 Combine like terms: 0 + 15 = 15 -23y = 15 Divide each side by '-23'. y = -0.652173913 Simplifying y = -0.652173913
| 20logk=60findk | | 3u/5=12 | | 7/6*u=42 | | 20logk=60 | | Y/11=10/20 | | 4.807+p=6.21 | | 3siny+7cosy=0 | | 38x+21y=360 | | 64+X-12=52 | | k/2−5=1 | | 44-7*x-3=13 | | m+2m-2m-m+3m=15 | | 3x-5=11x-56 | | 9x-1=-X+9 | | 3x^2+x=x | | X+(180-x)+105+75=360 | | 2x(x-2)=3(x+2) | | 4(f+1)= | | (4x-2)+(x+28)=180 | | 6x+7x+8x=42 | | 4y-7=x+28 | | 150x=28500 | | -1.7=2x | | 6x-1=16+3x | | (x-5)=18 | | 3x+ax+b=-3 | | 45x=30(40) | | 4x=5(5) | | (-4-4x)/(x^2-x-2) | | C(30)=30 | | y=0.4x+2 | | 8*2x+6=10(x+6) |